2015
DOI: 10.1186/s13027-015-0036-7
|View full text |Cite|
|
Sign up to set email alerts
|

Impact of human papillomavirus on head and neck squamous cell cancers in Gabon

Abstract: Head and neck squamous cell cancers are among the most aggressive. Their incidence and mortality rates are relatively lower in Middle Africa than worldwide, but in Gabon, these rates tend to be 2–3 fold higher than in neighboring countries. The main risk factors are alcohol and tobacco consumption. However, in the last decades, there was cumulated evidence that human papillomaviruses were a significant risk factor, particularly for oropharyngeal squamous cell cancer. In Gabon, as elsewhere in Africa, assessmen… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
5
0

Year Published

2016
2016
2018
2018

Publication Types

Select...
3

Relationship

1
2

Authors

Journals

citations
Cited by 3 publications
(5 citation statements)
references
References 21 publications
(21 reference statements)
0
5
0
Order By: Relevance
“…42 The low prevalence of high-risk HPV types in this study was associated with the uncommon practice of oral sex among the men studied in these regions. 42 Head and neck cancers in Nigeria show a peak incidence in the fourth decade of life with a male predominance and a younger age of onset than in white individuals. [43][44][45][46][47][48][49][50][51][52][53] The explanation for this finding might be rooted in genetic, behavioral, and socioeconomic risk factors.…”
Section: Incidence and Burden Of Hpv In Low-resourcementioning
confidence: 64%
See 2 more Smart Citations
“…42 The low prevalence of high-risk HPV types in this study was associated with the uncommon practice of oral sex among the men studied in these regions. 42 Head and neck cancers in Nigeria show a peak incidence in the fourth decade of life with a male predominance and a younger age of onset than in white individuals. [43][44][45][46][47][48][49][50][51][52][53] The explanation for this finding might be rooted in genetic, behavioral, and socioeconomic risk factors.…”
Section: Incidence and Burden Of Hpv In Low-resourcementioning
confidence: 64%
“…36 In South Africa, a pilot study showed a low prevalence rate (5.6%) of oral and oropharyngeal high-risk HPV (types 18 and 68) when compared to worldwide rates. 42 The prevalence of the high-risk HPV types was found to be positively associated with the number of oral sexual partners. 42 The low prevalence of high-risk HPV types in this study was associated with the uncommon practice of oral sex among the men studied in these regions.…”
Section: Incidence and Burden Of Hpv In Low-resourcementioning
confidence: 95%
See 1 more Smart Citation
“…After publication of this article [ 1 ], the authors noticed their names had been incorrectly reverted. The authors’ names were therefore incorrectly presented as: Labouba Ingrid, Bertolus Chloé, Koumakpayi Ismail Hervé, Belembaogo Ernest, Miloundja Jérôme and Berthet Nicolas.…”
mentioning
confidence: 99%
“…The correct presentations of the authors’ names are included in the author list of this erratum and have also been updated in the original article [ 1 ].…”
mentioning
confidence: 99%